Association between sports participation and resilience in school-attending students: a cross-sectional study - Sheng, Xinxin; Liang, Kaixin; Li, Kai; Chi, Xinli; Fan, Huiying (Frontiers in Psychology, 2024)
Aim: This research sought to identify the association between sports participation and resilience in children and adolescents as a means to enhance mental health.Methods: A comprehensive survey was carried out, encompassing primary, middle, and high school students from chosen educational institutions. The analytical sample comprised 67,821 students of school age. Sports participation and resilience were evaluated using validated assessment tools, while relevant covariates, such as sex and school grade, were assessed through self-reported questionnaires. Generalized Linear Models were applied to ascertain the association between sports participation and resilience for the entire sample, and separately for subgroups divided by gender or school grade, after controlling for covariates.Results: Among the 67,821 school students, males constituted 51.9% of the sample.Approximately 47.1% of the entire sample reported no sports participation, and the average resilience score was 24.7. The regression model analysis revealed that, in the entire sample, increased in sports participation was linked to higher resilience scores (odds ratio [OR] for 1-3 times per month: 1.20, 95%CI: 1.16-1.24; OR for 1-2 times per week: 1.38, 95%CI: 1.33-1.43; OR for 3 times or more per week: 1.72, 95%CI:1.65-1.79). Analyses stratified by gender and school grade indicated that sports participation was consistently associated with greater resilience.This study provides cross-sectional evidence supporting the positive association between sports participation and the resilience of children and adolescents, underscoring the potential of encouraging sports participation as a strategy for promoting mental health resilience. The findings presented herein should be subject to further confirmation or refutation in future research endeavors. OR: odds ratio; CI: confidence interval.Reference group for sports participation: never.